Penerapan Metode Modeling The Way dalam Proses Pengajaran : (Research dilakukan di MA PSM Sugiwaras Nganjuk) - ., Rumina; pengelola, pengelola (LPPM STAI Ihyaul Ulum Gresik, 2021)
The correct delivery of material is when students understand what we have to say and do the questions well, along with practicing it in everyday life. Departing from the teaching process for a teacher who is required to deliver material in accordance with the curriculum, so that teachers are required to use various methods or methods in teaching so that the delivery of material can run well. The application of the modeling the way method in MA PSM loceret Nganjuk, motivated by the understanding of students in the learning process and the teacher must be able to apply methods or strategies that are in accordance with the learning material and the use of appropriate methods. This type of research is descriptive, and MA PSM Loceret Nganjuk is used as a data source to get a portrait of the application of the modeling method applied by religion teachers focused on the subject of fiqh. The data were obtained by means of interviews and observations. The method of analysis used consists of three stages, namely data reduction, data presentation, and verification. From the results of the research conducted, the authors conclude that: Learning with the modeling the way method has worked quite well and students' attention can be focused on the child demonstrating the material, as well as providing practical experience that can form a strong memory. In addition, the supporting factors in The application of the modeling the way method at MA PSM Sugiwaras Nganjuk includes: teachers, students or students, learning methods, facilities and infrastructure, parents or guardians of students and the surrounding environment.